Functional Recovery and Serum Angiogenin Changes According to Intensity of Rehabilitation Therapy After Stroke - Garcia-Rodriguez, Nicolás; Rodriguez, Susana; Tejada, Pedro Ignacio; Miranda-Artieda, Zuberoa Maite; Ridao, Natalia; Buxó, Xavi; Pérez-Mesquida, María Engracia; Beseler, Maria Rosario; Salom, Juan B.; Pérez, Laura M.; Inzitari, Marco; Otero-Villaverde, Sergio; et al. (Frontiers in Neurology, 2021)
Background: Rehabilitation is still the only treatment available to improve the functional status after the acute phase of stroke. Most clinical guidelines highlight the need of designing rehabilitation treatments considering starting time, intensity or frequency, according to the patient's tolerance. However, there are no homogeneous protocols and the biological effects are under investigation. Objective: To investigate the impact of rehabilitation intensity (hours) after stroke on functional improvement and serum angiogenin (ANG) in a 6-months follow-up study. Methods: A prospective, observational, longitudinal and multicenter study with three cohorts: strokes in intensive rehabilitation therapy (IRT, minimum 15 hours/week) vs. conventional therapy (NO-IRT, less than 15 hours/week), and controls subjects (without known neurological, malignant, or inflammatory diseases). A total of 7 centers have participated with functional evaluations and blood sampling during follow-up. The final cohort includes 62 strokes and 43 controls with demographic, clinical, blood samples and an exhaustive functional monitoring. Results: The median (IQR) number of weekly hours of therapy was different: IRT 15 (15-16) vs NO-IRT 7.5 (5-9), p<0.01, with progressive and significant improvements in both groups. However, IRT patients showed earlier improvements (within one month) on several scales (CAHAI, FMA and FAC; p<0.001) and earliest community ambulation achievements (0.89 m/s at 3 months). The serum ANG level was influenced by the intensity of therapy, peaking at one month only in the IRT group (p<0.05) whereas it decreased in the NO-IRT group (p<0.05). Conclusions: Our results suggest an association of rehabilitation intensity with early functional improvements, and connect the rehabilitation process with blood biomarkers.